(untitled) (CIPEEX, 2025)
Shift work in industry compromises the circadian cycle, impairing sleep quality (SQ), increasing levels of fatigue and attention deficit, which negatively impacts productivity and professional performance. The objective of this review was to verify in the literature whether shift work affects the QS of industrial workers. This is a systematic review that was conducted using the PRISMA guideline criteria. The inclusion criteria were studies that used the Pittsburgh scale, stratified the sample by shift, were written in English, were original, and were published in the last five years. At the time of the search, 276 studies were found, but only three were selected for this review. The workers were aged between 18 and 41 years, and the Pittsburgh Index scores for daytime work were between 5.7 and 8.8 points, while those for night work were between 3.6 and 7.8 points. However, two studies reported less favorable QS among workers. Although the results were inconclusive, two studies identified worse QS among workers who work different shifts.